2007
DOI: 10.1177/000313480707300405
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Initial Margin Status for Invasive Breast Cancer and Residual Carcinoma after Re-Excision

Abstract: Little data exists addressing the relationship between initial margin status in a specimen from an excisional biopsy and the presence of residual carcinoma in a subsequent specimen from lumpectomy or mastectomy. We sought to determine the relationship between initial margin status and the presence of residual invasive cancer, and to identify any relationship to other variables. This study was a retrospective review of pathology reports of 582 early-stage invasive duct carcinomas with open excisional biopsies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Although some studies have shown a strong, inverse correlation between the risk for local recurrence and the distance between the surgical margin and the tumor , others have not found this correlation . The National Comprehensive Cancer Network (NCCN) Guidelines have historically defined a 2 mm surgical margin as adequate to prevent recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have shown a strong, inverse correlation between the risk for local recurrence and the distance between the surgical margin and the tumor , others have not found this correlation . The National Comprehensive Cancer Network (NCCN) Guidelines have historically defined a 2 mm surgical margin as adequate to prevent recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…First, DUV-FSM can image large margins of variable size with subcellular resolution. Since the size of lumpectomy margins varies and most positive margins typically involve small microscopic foci of cancer, [51] a device with both large margin coverage and microscopic resolution is highly desirable to rapidly evaluate lumpectomy margin status intraoperatively with both low false-negative and false-positive rates. However, many technologies currently under investigation are either a point device (e.g., optical spectroscopy, i-Knife, MarginProbe) or a high resolution device with very small eld of view (e.g., OCT, confocal) that requires excessive time to manually scan a surgical margin, or a wide-eld imaging device with very low spatial resolution (e.g., uorescence imaging, SFDI).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies agreed that multifocality of tumors, infiltrative tumor borders, large tumor size, and younger age predict re-excision (Devouge et al, 2013;Jung et al, 2012;Lovrics et al, 2009;Meier-Meitinger et al, 2012). Some studies also link palpable tumors to increased risk for positive margins (Kotwall, Ranson, Stiles, & Hamann, 2007;Lovrics et al, 2009).…”
mentioning
confidence: 94%